Lexical-semantic Group with the Root -kras- in Ukrainian Lingvo-cultural Space (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper deals with the composition of the lexical-semantic group with the root ‑kras- in Ukrainian lingvo-cultural space, denoted by different discourses. The historic succession and functional significance of the analyzed items in formation of fragments of the national language picture of the world are emphasized. The attention is paid to semantic polyphony of the nomination and dominance of esthetic valuation in contemporary meanings of the words of different topical groups.
Keywords: lexical-semantic group; nomination; meaning; valuation; folk language; lingvo-cultural space